Analisis Penguasaan Kosakata Terhadap Efektivitas Menulis Teks Negosiasi pada Siswa Kelas X MAN Kota Mojokerto - Reisya Diva Maharani Putri; Asih Andriyati Mardliyah; Rani Jayanti (Jurnal Kajian Ilmu Pendidikan, Bahasa dan Komunikasi, 2025)
Writing is a complex and fundamental language skill that plays a central role in developing students’ literacy, particularly in the context of producing negotiation texts. Negotiation texts are one of the text types taught in the Indonesian language curriculum that demand mastery of varied vocabulary, logical coherence, and persuasive language structures. Despite its importance, many students continue to face challenges in composing negotiation texts effectively. Difficulties are often found in choosing the right vocabulary, applying grammatical rules accurately, and constructing arguments that are logically consistent and persuasive. This study aims to analyze the extent to which students’ mastery of Indonesian vocabulary and grammar contributes to their ability to write negotiation texts. The research was conducted on class X students of MAN Kota Mojokerto using a qualitative method with a descriptive approach. Data were collected through three techniques: analysis of students’ written negotiation texts, interviews with teachers and students, and classroom observations during the learning process. The results of the study reveal that most students demonstrate limited mastery of vocabulary, which results in repetitive word choices and restricted expression. In addition, weaknesses in grammar application often lead to inaccurate sentence construction, lack of cohesion, and unclear argument flow. These shortcomings significantly affect the quality of negotiation texts, which tend to be less persuasive, poorly structured, and unable to fulfill the standard criteria of negotiation text writing. Based on these findings, it can be concluded that vocabulary mastery and grammar proficiency play a crucial role in supporting students’ negotiation text writing skills. To address this issue, Indonesian language learning needs to adopt strategies that consistently emphasize writing practice, provide opportunities for vocabulary enrichment, and strengthen students’ grammatical competence. Such approaches are expected to improve students’ literacy levels, particularly in the production of negotiation texts.